2008
DOI: 10.1143/jjap.47.4651
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Thermal Migration of Eu Ion Doped into TiO2 Nanoparticles

Abstract: The location of the Eu ion in the TiO 2 lattice was investigated as a function of sintering temperature using X-ray photoelectron spectroscopy (XPS), to clarify the role of the Eu ion in TiO 2 nanoparticles synthesized by the simple sol-gel method. The crystalline structure as well as the average crystallite size were evaluated using X-ray diffraction (XRD), and the direct observation of nanoparticles was carried out using atomic force microscopy (AFM). A model was proposed in which, in the as-synthesized gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…The rutile phase appears at sintering temperatures above 950 C in 1 mol % Eu 3þ -doped titania, while it appears at temperature above 700 C in non-doped titania. 28) This is consistent with our results for Eu500, Eu900, TiO 2 500, and TiO 2 900. Figure 3 shows absorption spectra of Eu500, Eu900, TiO 2 500, and TiO 2 900 nanoparticles at room temperature, all of which are similar to each other.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…The rutile phase appears at sintering temperatures above 950 C in 1 mol % Eu 3þ -doped titania, while it appears at temperature above 700 C in non-doped titania. 28) This is consistent with our results for Eu500, Eu900, TiO 2 500, and TiO 2 900. Figure 3 shows absorption spectra of Eu500, Eu900, TiO 2 500, and TiO 2 900 nanoparticles at room temperature, all of which are similar to each other.…”
Section: Methodssupporting
confidence: 93%
“…It has, however, been observed in X-ray photoelectron spectroscopy (XPS) that the Eu 3þ ions have the tendency to locate near the surface. 28) We tried to find different PL spectra between the two samples. When Eu900 was excited at 290 nm or shorter wavelengths, we observed that a weak broad band spectrum was superposed on a sharp line spectrum as shown in Spectrum (4) of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At temperatures above 900 1C, the Eu 3+ ions migrate to the surface and form Eu 2 Ti 2 O 7 . 107 The photoluminescence abruptly decreases due to the formation of the pyrochlore structure; this was confirmed in a subsequent study. 108 The luminescent and thermal property of Eu-TiO 2 fiber prepared by electrospinning was studied by Bianco et al The emission spectrum was dominated by the 5 D 0 to 7 F 2 transition and the broadness of the peak suggested an inhomogeneous distribution of the Eu 3+ ion.…”
Section: Europium Modified Tio 2 Photocatalystssupporting
confidence: 63%
“…Both of these effects can be attributed to the anatase-to-rutile phase transformation, as the lattice volume shrinks during this transformation and causes the Dy 3+ ions to be ejected from lattice sites. These ejected Dy 3+ ions can then result in the formation of a secondary phase, which most likely has poorer PL properties. , …”
Section: Results and Discussionmentioning
confidence: 99%